Screen Time vs. Speaking Time: A Qualitative Comparison of Speech Development in Toddlers with Different Gadget Use Patterns - Al Baqi, Safiruddin; Afiah, Nur (Islamic Early Childhood Education Study Program, Faculty of Tarbiyah and Education, UIN Sunan Kalijaga Yogyakarta, 2025)
Purpose – This study investigates how different gadget use patterns affect toddler speech develop-ment, addressing concerns about passive screen time limiting verbal interaction opportunities.Design/methods/approach – A qualitative case study design was used to gain in-depth insights into children’s behavior in their social context. Participants were selected purposively based on parental reports of gadget use. Inclusion criteria were toddlers aged 1 year 8 months to 4 years (M = 2.75 years) with typical development and no diagnosed disorders. Exclusion criteria included neurological conditions and prior speech-language therapy. The final sample consisted of 16 toddlers (7 girls, 9 boys), categorized into intensive users (frequent, prolonged exposure to non-interactive content) and limited users (gadgets used mainly for calls or video chats with relatives). Data collection included semi-structured parent interviews (30–45 minutes), naturalistic observation, and developmental screenings by a licensed child psychologist. Validity was ensured through triangulation and member checking. Data were analyzed using thematic analysis involving coding, categorization, and theme development.Findings – Thematic analysis identified three key themes: rich verbal interaction fosters early speech, passive screen exposure hinders language acquisition, and early or unsupervised gadget use disrupts developmental timing. Children with limited gadget use developed age-appropriate speech, used spontaneous verbal expressions, and required no speech therapy. In contrast, toddlers with intensive gadget use showed limited vocabulary, reduced responsiveness, and in many cases required speech therapy. These developmental disparities were closely linked to differences in caregiver interaction, content type, and exposure duration.Research implications/limitations – This study offers contextual insight from Indonesia using triangulated qualitative methods, though its small sample limits generalizability. Broader, mixed-method studies are recommended.Practical implications – The findings emphasize limiting passive gadget use and encouraging active verbal interaction. Parenting programs and early education should promote language-rich environments and conscious media use. Digital tools should support interactive, not passive, use. Early intervention, including parental involvement and therapy, is essential.Originality/value – This study adds to the discourse on early media exposure by offering practical insights for parents, educators, and policymakers to support toddlers’ speech development.Paper type Research paper